2009
DOI: 10.2136/sssaj2008.0113
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter Effects on Phosphorus Sorption: A Path Analysis

Abstract: While P sorption in mineral soils has been extensively studied, P sorption behavior in organic‐rich soils is less known. This study was conducted to determine the relationships between Langmuir P sorption maxima (Smax) and selected physicochemical properties of soils, with particular emphasis on organic matter (OM) content. The Smax values were determined for 72 soil samples from the North Carolina Coastal Plain, along with pH, clay and OM contents, oxalate‐extractable P (Pox), Al (Alox), and Fe (Feox), and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 41 publications
7
83
2
1
Order By: Relevance
“…The soil properties that had the greatest influence on the b parameters were soil texture, pH, Ca, Al, and Fe. Soil OM was not a significant factor for the b parameter, which contradicts the results of Kang et al (2009) and Weng et al (2012), who reported that high OM levels would minimize a soil's ability to adsorb P from a solution.…”
Section: Chemical Sequential Fractionationcontrasting
confidence: 85%
See 1 more Smart Citation
“…The soil properties that had the greatest influence on the b parameters were soil texture, pH, Ca, Al, and Fe. Soil OM was not a significant factor for the b parameter, which contradicts the results of Kang et al (2009) and Weng et al (2012), who reported that high OM levels would minimize a soil's ability to adsorb P from a solution.…”
Section: Chemical Sequential Fractionationcontrasting
confidence: 85%
“…Other researchers have also reported that P sorption in soils is dependent on pH, Ca, the initial P status of the soils, and OM (Weng et al, 2012;Perassi and Borgnino 2014). However, Kang et al (2009) andWeng et al (2012) reported that dissolved OM in soil can reduce the sorption potential of a soil because of its interaction with Al and Fe, which would otherwise sorb P from solution and organic compounds can out-compete phosphate groups for biding sites. In our study, soil OM also had a negative impact on the k i and k f parameters (Table 1 and Table 2).…”
Section: Chemical Sequential Fractionationmentioning
confidence: 99%
“…These relationships may be partly because that labile P is largely derived from the decomposition of organic matter (Tiessen et al 1994;Johnson et al 2003). Soil organic matter can also absorb labile Pi via poorly crystalline or non-crystalline Al and Fe (Kang et al 2009), as supported by the strong correlation between soil organic C content and P sorption index in our study (Fig. 3).…”
Section: Relationship Between Soil Organic C Content and Soil P Fractsupporting
confidence: 73%
“…Soil organic matter provides an important source of P that can be utilised by plants and soil microbes following mineralisation (Tiessen et al 1994;Kirkby et al 2011), as well as energy reserves and carbon (C) substrates used in microbial activities such as the production of enzymes involved in P mineralisation (Allison and Vitousek 2005;Allison et al 2007). It can also maintain soil P availability by providing binding sites (Kang et al 2009). However, some studies have suggested that an accumulation of soil organic C (or organic matter) may decrease soil P availability due to the inclusion of P in organic form (Huang et al 2012;Schlesinger et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation coefficient is not large but the spatial distribution pattern of phosphorus ( Figure 5) indicates that the phosphorus is relatively more deficient in high clay area. Several studies have shown significant effect of soil clay content on phosphorus sorption [3][4][5]. High surface area and presence of various P sorbing minerals that results in the common observation that high clay soils often adsorb more P compared with coarse-textured soils.…”
Section: Citationmentioning
confidence: 99%